The feasibility and safety of his-purkinje conduction system pacing in patients with heart failure with severely reduced ejection fraction - Ma, Chengming; Wang, Zhongzhen; Ma, Zhulin; Ma, Peipei; Dai, Shiyu; Wang, Nan; Yang, Yiheng; Li, Guocao; Gao, Lianjun; Xia, Yunlong; Xiao, Xianjie; Dong, Yingxue (Frontiers in Cardiovascular Medicine, 2023)
Objective The purpose of this study was to evaluate the feasibility and outcomes of conduction system pacing (CSP) in patients with heart failure (HF) who had a severely reduced left ventricular ejection fraction (LVEF) of less than 30% (HFsrEF). Methods Between January 2018 and December 2020, all consecutive HF patients with LVEF < 30% who underwent CSP at our center were evaluated. Clinical outcomes and echocardiographic data [LVEF and left ventricular end-systolic volume (LVESV)], and complications were all recorded. In addition, clinical and echocardiographic (≥5% improvement in LVEF or ≥15% decrease in LVESV) responses were assessed. The patients were classified into a complete left bundle branch block (CLBBB) morphology group and a non-CLBBB morphology group according to the baseline QRS configuration. Results Seventy patients (66 ± 8.84 years; 55.7% male) with a mean LVEF of 23.2 ± 3.23%, LVEDd of 67.33 ± 7.47 mm and LVESV of 212.08 ± 39.74 ml were included. QRS configuration at baseline was CLBBB in 67.1% (47/70) of patients and non-CLBBB in 32.9%. At implantation, the CSP threshold was 0.6 ± 0.3 V @ 0.4 ms and remained stable during a mean follow-up of 23.43 ± 11.44 months. CSP resulted in significant LVEF improvement from 23.2 ± 3.23% to 34.93 ± 10.34% (P < 0.001) and significant QRS narrowing from 154.99 ± 34.42 to 130.81 ± 25.18 ms (P < 0.001). Clinical and echocardiographic responses were observed in 91.4% (64/70) and 77.1% (54/70) of patients. Super-response to CSP (≥15% improvement in LVEF or ≥30% decrease in LVESV) was observed in 52.9% (37/70) of patients. One patient died due to acute HF and following severe metabolic disorders. Baseline BNP (odds ratio: 0.969; 95% confidence interval: 0.939–0.989; P = 0.045) was associated with echocardiographic response. The proportions of clinical and echocardiographic responses in the CLBBB group were higher than those in the non-CLBBB group but without significant statistical differences. Conclusions CSP is feasible and safe in patients with HFsrEF. CSP is associated with a significant improvement in clinical and echocardiographic outcomes, even for patients with non-CLBBB widened QRS.